Ascertaining the refrigerated storage life of wheat bran and grape seed extract enriched meatballs (Goshtaba) under aerobic conditions: Ascertaining the refrigerated storage life - Sajad, Sadiya; Ahmad, Sheikh Rafeh; Wani, SA; Sofi, AH; Farooq, J; Khan, AA; Hussain, SA; Masoodi, FA; Irshad, S; Nazir, T (Journal of Meat Science, 2023)
Three types of meatballs (Goshtaba) viz. control, dietary fiber (8% hydrated wheat bran) rich and anti-oxidant rich (0.1% grape seed extract) Goshtaba were prepared from good quality mutton, packaged in low density polyethylene pouches (LDPE-200µm gauge) and analyzed during its refrigerated storage (4±1◦C) to ascertain their aerobic refrigerated storage life. The emulsion stability and cooking yield of the dietary fiber rich product was improved. The pH of dietary fiber rich product increased significantly (P≤0.05), while as that of antioxidant rich Goshtaba decreased significantly (P≤0.05) with the increase in the storage period. The water activity of all the samples showed an increasing trend over the storage period. The microbial parameters (total plate count, psychrophilic count) increased during the storage period, but the values were decreased in the product fortified with grape seed extract (GSE), depicting an anti-microbial effect of GSE. The sensory quality was decreased in all the products with increase in storage life, but the rate of decline was slowest in GSE treated meatballs. It was concluded that the product treated with GSE as anti-oxidant source retained most of the desirable properties during the aerobic refrigerated storage for at least 26 days as against 17 days in case of other products.